2022
DOI: 10.1038/s41597-022-01374-7
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregated data on age and sex for the first 250 days of the COVID-19 pandemic in Bucharest, Romania

Abstract: Experts worldwide have constantly been calling for high-quality open-access epidemiological data, given the fast-evolving nature of the COVID-19 pandemic. Disaggregated high-level granularity records are still scant despite being essential to corroborate the effectiveness of virus containment measures and even vaccination strategies. We provide a complete dataset containing disaggregated epidemiological information about all the COVID-19 patients officially reported during the first 250 days of the COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…1,[12][13][14][15] Recent reports have suggested a worse prognosis among male patients, 13 and some authors have shown an increased tendency of hospitalization and ICU admission associated with African-Americans/ blacks. 12,16,17 Nonetheless, there is a lack of studies addressing sex differences and race amidst Brazilian cases of COVID-19.…”
Section: 2023mentioning
confidence: 99%
“…1,[12][13][14][15] Recent reports have suggested a worse prognosis among male patients, 13 and some authors have shown an increased tendency of hospitalization and ICU admission associated with African-Americans/ blacks. 12,16,17 Nonetheless, there is a lack of studies addressing sex differences and race amidst Brazilian cases of COVID-19.…”
Section: 2023mentioning
confidence: 99%
“…Interestingly, females are slightly more likely to test positive than males [ 4 ]. Data on gender for the first 250 days of the COVID-19 pandemic in Bucharest, Romania showed that 53.2% of COVID-19 cases were females, and gender and age data should influence the prevention measures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 One recent example of a disease outbreak where estimating prevalence was challenging is COVID-19. [8][9][10][11] This outbreak was characterized by high infection rates, but with frequently asymptomatic cases particularly in vaccinated individuals. Most estimates of population-level prevalence were derived from voluntary testing regimes, using either PCR or antigen test, where the incentives for choosing to be tested varied between individuals (e.g., desire to prevent transmission to clinically vulnerable relatives) and over time (e.g., varying requirements for being tested at workplaces, to enter bars/theatres/restaurants, or before travel).…”
Section: Introductionmentioning
confidence: 99%
“…One recent example of a disease outbreak where estimating prevalence was challenging is COVID‐19 8–11 . This outbreak was characterized by high infection rates, but with frequently asymptomatic cases particularly in vaccinated individuals.…”
Section: Introductionmentioning
confidence: 99%